1989
DOI: 10.1073/pnas.86.24.9642
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a bifunctional enzyme: 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase.

Abstract: The bifunctional rat liver enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (ATP:Dfructose-6-phosphate 2-phosphotransferase/D-fructose-2,6-bisphosphate 2-phosphohydrolase, EC 2.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 49 publications
1
68
2
Order By: Relevance
“…Alignment of amino acid sequences of acid phosphatases (Roiko et al, 1990;Van Etten et al, 1991) has revealed a conserved sequence motif RHGXRXP. The RHG sequence is also found in phosphoglycerate mutase and 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase which suggested that these three enzymes might share a common fold (Bazan et al, 1989). Recent crystallographic studies Lindqvist et al, 1993) of native rat prostatic acid phosphatase and its complex with the inhibitor L(+)-tartrate have shown that the structure of acid phosphatase consists of two domains, an utP domain consisting of a seven-stranded mixed P-sheet with a-helices on both sides of the sheet, and a smaller ahelical domain.…”
mentioning
confidence: 98%
“…Alignment of amino acid sequences of acid phosphatases (Roiko et al, 1990;Van Etten et al, 1991) has revealed a conserved sequence motif RHGXRXP. The RHG sequence is also found in phosphoglycerate mutase and 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase which suggested that these three enzymes might share a common fold (Bazan et al, 1989). Recent crystallographic studies Lindqvist et al, 1993) of native rat prostatic acid phosphatase and its complex with the inhibitor L(+)-tartrate have shown that the structure of acid phosphatase consists of two domains, an utP domain consisting of a seven-stranded mixed P-sheet with a-helices on both sides of the sheet, and a smaller ahelical domain.…”
mentioning
confidence: 98%
“…Because this enzyme controls the cellular concentration of fructose-2,6-bisphosphate (Fru-2,6-P 2 ), which is the most potent allosteric activator of phosphofructokinase, the rate-limiting enzyme of glycolysis, PFKFB eventually controls the glycolytic rate (1)(2)(3). The bifunctional enzyme acutely controls the concentration of Fru-2,6-P 2 by modulating the two mutually exclusive catalytic activities of Fru-2,6-P 2 synthesis (2-Kase) and hydrolysis (2-Pase) that reside in the two separate domains (4,5). The two activities are exquisitely regulated by various metabolic products and signal transduction-dependent phosphorylation such that the resulting predominant activity determines the final concentration of Fru-2,6-P 2 and, ultimately, the rates of glycolysis (6 -9).…”
mentioning
confidence: 99%
“…Shaded boxes contain conserved catalytic and substrate binding sites [12]. Using numbering based on rat liver sequence, these sites include: Arg452, Lys-356, and Arg-360, residues shown to bind substrate and/or product which are found on a surface loop of all mammalian FBPases; His-258, Glu-327 and His-392, a trio of catalytic residues in rat liver [30,12]; Arg-195, a key residue involved in Fru-6-P binding [31]; Arg-257 and Arg-307, which associate with the reactive C-2 phospho group of Fru-2,6-P2 [30,32]; and the ATP binding site, GlyLeu-Pro-Ala-Arg-Gly-Lys-Thr [33]. Underlined residues represent potential phosphorylation sites.…”
Section: Discussionmentioning
confidence: 99%